2020
DOI: 10.1093/sleep/zsaa056.310
|View full text |Cite
|
Sign up to set email alerts
|

0313 Is Healthy Sleep Possible for Professional Firefighters? A Comparison of “On-Duty” and “Off-Duty” Sleep Quantity and Quality

Abstract: Introduction Healthy sleep is vital for firefighter safety, health, wellness, and for public well-being. However, professional firefighters experience disturbed sleep at disproportionately high rates. The current study investigated whether firefighters can obtain healthy sleep by identifying (1) differences in sleep while “on-duty” and “off-duty” and (2) risk factors for poor sleep. Methods Professional firefighters in Richmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The various validated questionnaires, applied to 196 participants, revealed that 6.9% of the firefighters had poor sleep quality, 27.7% showed excessive daytime sleepiness, 18.8% reported moderate to severe symptoms of insomnia, and 1.6% had moderate to high risk of obstructive sleep apnea. These results confirm the overall literature [67][68][69][70][71] showing that poor sleep quality and sleep disturbances are present in the firefighting work class. The Firesleep program was sufficient at establishing the association between certain risk factors and quality of sleep.…”
Section: Sleep Crossover and Observation Trialssupporting
confidence: 91%
“…The various validated questionnaires, applied to 196 participants, revealed that 6.9% of the firefighters had poor sleep quality, 27.7% showed excessive daytime sleepiness, 18.8% reported moderate to severe symptoms of insomnia, and 1.6% had moderate to high risk of obstructive sleep apnea. These results confirm the overall literature [67][68][69][70][71] showing that poor sleep quality and sleep disturbances are present in the firefighting work class. The Firesleep program was sufficient at establishing the association between certain risk factors and quality of sleep.…”
Section: Sleep Crossover and Observation Trialssupporting
confidence: 91%
“…Despite this, future studies should utilize longitudinal designs to confirm the present findings. Secondly, the items we utilized for our assessment of sleep health—although in line with common procedures (Dautovich et al, 2020; Savall et al, 2021)—did not capture the full spectrum previously discussed. That is, they did not account for distinctions between off duty and on duty sleep nor did they capture call volume or severity.…”
Section: Discussionmentioning
confidence: 99%